Bathyferula, a new Caribbean deep-water turrid genus (Gastropoda: Turroidea), with description of a large-sized new species - Stahlschmidt, Peter; Lamy, Dominique; Fraussen, Koen (Zootaxa, 2012)
The examination of five specimens of a turrid species from various Caribbean locations led us to the recognition of a new species and genus. Although the group of turriform gastropods comprise already about 340 valid genera and subgenera (Taylor et al. 1993) we have not been able to find a genus that, even in a very broad sense, could accommodate the new species. Therefore, we propose the new genus Bathyferula.